Curadoria Digital e Gênero na Ciência da Informação - Jorente, Maria José Vicentini (Editora Oficina Universitária, 2021)
The world of presences is simulated, presented and represented in the digital medium. In the context of digital-virtual communication, and from the recent transformations in its supports, the multimodal collections of information move to a state in which the access of informational subjects to information can be facilitated and expanded. In such a universe, the information and data represented need conceptual and technical treatments that respect the nature and particularities of the means and languages that transit through them. In addition, as they are processed in a fragile medium such as digital, information encoded for electronic media also requires procedures and care aimed at its integral preservation. In Information Science, the set of continuous and iterative procedures with a view to meeting care demands to optimize access and preservation is called Digital Curation: a complex of processes that include from initial design and conceptualization, to the assignment of metadata, the evaluation preservation or disposal decisions, transformation, access, sharing and re-evaluation of digital objects. When it comes to gender, conditions become more acute, as the need for Digital Curation becomes more pressing when we are faced with dramatic events that concern its multiple territories. In them, the information must deal with the sociocultural purpose of being able to create strategies and instruments to overcome the countless challenges and present injustices. The book Digital Curation and Gender in Information Science: access and preservation seeks, through the combined vision of authors from the national and international panorama, to deal with themes concerning some gender issues in the perspective of improvements provided by Digital Curation actions; and the particularities of preservation and access that apply.